Use of Removable Partial Denture in Child with Papillon-Lefevre Syndrome: Case Report - Saskianti, Tania; Ramadhani, Karina; Ainayah, Aulia Nuur; Dewi, Ardianti Maartrina (Indonesian Journal of Dental Medicine, 2019)
Background: Papillon-Levefre Syndrome (PLS) is a rare genetic disorder with prevalence of 1-4 cases per millions of birth, characterized by the presence of palmar-plantar hyperkeratosis and rapid periodontal destruction of both the primary and secondary dentition. Purpose: This clinical report described such a rare condition with special attention on its diagnostic characterization, various treatment options and Prosthodontic rehabilitation. Case: Five years-old boy accompanied by his mother came to Pediatric Dentistry Specialist Clinic, Universitas Airlangga Dental Hospital - Surabaya with the chief complaint of gradually loss of upper and lower teeth since the patient was 3 years old. Case Management: Removable partial denture was chosen because it was considered as an appliance that can recover the function of mastication, speech and aesthetic patient. Removable partial denture was designed to replace 51, 52, 53, 54, 55, 61, 62, 63, 64, 65, 72, 73, 74, 75, 82, 83, 84 and 85 with retention on 16, 26, 36 and 46, and anterior bite riser on 31 and 41. Conclusion.Removable partial denture is the treatment of choice for children with PLS who are still in the growth period because it can recover mastication and aesthetic functions, have a good aesthetic, and easy maintenance that could done by the child.